The Medieval Archive of Antisemitism in Nineteenth-Century Sweden - Heß, Cordelia (Religious Minorities in the North, 2021)
This book is the first study of the development of antisemitism in nineteenth-century Sweden, based on an analysis of 150 books and pamphlets. The significance of religion for the development of modern racist antisemitism is a much debated topic - the Swedish case provides new insights into this debate. Relying on medieval models, nineteenth-century debates were informed by a comprehensive and mostly negative "knowledge" about Jews.